In-line Mach-Zehnder interferometer composed of microtaper and long-period grating in all-solid photonic bandgap fiber - Wu, Zhifang (2013)
We report a compact in-line Mach-Zehnder interferometer combining a microtaper with a longperiod grating (LPG) in a section of all-solid photonic bandgap fiber. Theoretical and experimental investigations reveal that the interferometer works from the interference between the fundamental core mode and the LP01 cladding supermodes. The mechanism underlying the mode coupling caused by the microtaper can be attributed to a bandgap-shifting as the fiber diameter is abruptly scaled down. In addition, the interferometer designed to strengthen the coupling ratio of the longperiod grating has a promising practical application in the simultaneous measurement of curvature and temperature.